Thermoanalytical Investigation of Terazosin Hydrochloride - Mona Mohamed Abdel-Moety; Ali Kamal Attia (Tabriz University of Medical Sciences, 2013)
Purpose: Thermal analysis (TGA, DTG and DTA) and differential scanning calorimetry (DSC) have been used to study the thermal behavior of terazosin hydrochloride (TER). Methods: Thermogravimetric analysis (TGA/DTG), differential thermal analysis (DTA) and differential scanning calorimetry (DSC) were used to determine the thermal behavior and purity of the used drug. Thermodynamic parameters such as activation energy (E*), enthalpy (H*), entropy (S*) and Gibbs free energy change of the decomposition (G*) were calculated using different kinetic models. Results: The purity of the used drug was determined by differential scanning calorimetry (99.97%) and specialized official method (99.85%) indicating to satisfactory values of the degree of purity. Thermal analysis technique gave satisfactory results to obtain quality control parameters such as melting point (273 ºC), water content (7.49%) and ash content (zero) in comparison to what were obtained using official method: (272 ºC), (8.0%) and (0.02%) for melting point, water content and ash content, respectively. Conclusion: Thermal analysis justifies its application in quality control of pharmaceutical compounds due to its simplicity, sensitivity and low operational costs. DSC data indicated that the degree of purity of terazosin hydrochloride is similar to that found by official method.